Asia's new regionalism and global role agenda for the East Asia Summit - Kumar, Nagesh 1958-; Kesavapany, K.; Chaocheng, Yao (Research and Information System for Developing Countries, 2008)
Contributed articles presented at a series of conferences held at various places between 2004-2005.